PERANCANGAN MOTION GRAPHIC TAMBO ALAM ASAL USUL NENEK MOYANG MINANGKABAU SEBAGAI MEDIA PEMBELAJARAN BUDAYA ALAM MINANGKABAU - SULAIMAN SALEH, Dini Faisal, S.Ds., M.Ds., Henra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The Developing of Curriculum at elementary school nowadays has demanding the students to be more focused to their main lessons, with the result that their cultural lessons slowly fading throughout the time, The using of motion graphic to introduce them Tambo of Minangkabau on elementary school is the creative idea to make the cultural lessons are still interesting for elementary school students. The Description of Tambo with Motion graphic are one of thestrategies to draw enthusiasm of the elementary school students in studying Minangkabau’s Culture.The Motion graphic’s Design of The Tambo Alam the Origin of Minangkabau’s Ancestors as a Learning Media of Minangkabau Culture with Glass Box Method, which is attempting to find the Facts, or the Cause also the Factual Reason of the main cause of an event to find some alternate solutions upon the facing problems. The Design is doing by multiple stages such as collecting data, analysis and Design data. The Data Gathering are doing by interviews, While the Analysis are using 5W+1H, obtained by gathering data from Observation.The Design of Minangkabau Tambo’s Motion graphic will produce a media such as Animated  Video in form of Motion graphic, with its function as the media in learning process of  Minangkabau Culture. The Design also supported with some other medias such as: Poster, Cover DVD, Note Book, T-shirt, Mug, Sticker and, X-Banner.Key Word: Motion graphic, Tambo Alam, Minangkabau, Media Pembelajaran